1998
DOI: 10.1097/00004032-199810000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Of Physico-Chemical And Biokinetic Properties Of Uranium Peroxide Hydrate UO4

Abstract: Comprehensive studies on the radiotoxicological risk of an intermediate compound UO4, which is not specified in ICRP Recommendations, were motivated by its increased use in the nuclear fuel cycle and the lack of information such as physico-chemical and biokinetic properties. The aim of this work was to give an experimental basis for assessing the appropriate limits on intake for workers exposed to UO4 and to provide guidance for the interpretation of personal monitoring data. Particle size measurement of the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…In our study, the UO 4 biokinetics after single UO 4 inhalation (AcUO4 group) agreed with previous UO 4 instillation studies (Ansoborlo et al, 1998;Houpert et al, 1999;Chazel et al, 2001). A rapid clearance of U from lungs resulted partly from its translocation to the blood, and U was subsequently excreted in the urine.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, the UO 4 biokinetics after single UO 4 inhalation (AcUO4 group) agreed with previous UO 4 instillation studies (Ansoborlo et al, 1998;Houpert et al, 1999;Chazel et al, 2001). A rapid clearance of U from lungs resulted partly from its translocation to the blood, and U was subsequently excreted in the urine.…”
Section: Discussionsupporting
confidence: 91%
“…A rapid clearance of U from lungs resulted partly from its translocation to the blood, and U was subsequently excreted in the urine. Both our inhalation study and a previous instillation study, with comparable lung deposit (around 200µg), showed a UO 4 peak in kidneys of about 15% of the intake, at 3 days postexposure (Ansoborlo et al, 1998). The previous UO 2 exposures apparently modify the early UO 4 biokinetics in kidneys without modifying the day of appearance of the UO 4 peak in kidneys.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Ansoborlo et al (1998a) used two different media (Gamble's solution and culture medium) for the solubility tests. The dissolution rate for the slow fraction of the material in Gamble's solution (an alternative to simulated lung fluid) was lower by a factor of 30.…”
Section: Determination Of Parameter Valuesmentioning
confidence: 99%
“…1 For pulmonary toxicity studies, specialized equipment that includes aerosol generators, airflow monitoring instruments, exposure chambers, exhaust systems and often analytical chemical support is required in order to deliver known amounts of the test compound into the lungs. Consequently, the need for this equipment increases the cost and technical complexity of such studies.…”
mentioning
confidence: 99%